Peran Media Visual Dalam Mengembangkan Keterampilan Menulis Teks Narasi Dan Deskripsi Di Sekolah - Anita Candra Dewi (FKIP UNSULTRA, 2025)
Writing is a fundamental skill in Indonesian language learning, particularly in narrative and descriptive text production. However, many students struggle with generating ideas, organizing paragraphs, and constructing coherent sentences. One promising approach to address these issues is the integration of visual media in writing instruction. This literature review aims to explore the role of visual media in enhancing students' writing skills, specifically in composing narrative and descriptive texts. Data were gathered from a range of scholarly sources, including books, journals, and research articles published within the last ten years. The findings indicate that visual mediasuch as images, videos, comics, and illustrations effectively stimulate students’ imagination, simplify contextual understanding, and support text structure development. Additionally, visual media significantly increase students’ motivation and engagement in the writing process. This study recommends that visual media be incorporated as an integral component of writing instruction, especially at the elementary and secondary education levels.